FREQUENCIES AND COLLOCATIONS OF DEICTIC VERBS COME AND GO - Ratri, Ayu (UC Journal: ELT, Linguistics and Literature Journal, 2023)
The focus of this study was to explore the frequencies and collocations analysis in Contemporary American English for the verbs come and go. To conduct the study, the researchers employed quantitative and qualitative methods. Data were collected from the Corpus of Contemporary American English (COCA) and analyzed using Benson et al.'s (1986; 2010) grammatical and lexical collocation types. COCA stores all tokens of academic, fiction, movies, blogs, newspapers, and magazine domains. All occurrences frequency of COCA was retrieved, and 300 tokens consisting of the words come and go were collected. The results showed that the word deictic go was more frequent than the word come in COCA, with a total frequency of occurrence of 55% and 45%, respectively. The type of collocation in the word go also had more variations. The word go had nine types of collocation, whereas the word come had seven types of collocations. This study gives applicable and relevant knowledge to non-native speakers of English.